Bilateral in vivo assessment of mandibular chewing dynamics using multi-slice real-time MRI: the rotation-translation-ratio in normal and displaced TMJ discs - Paddenberg, Eva; Kubein-Meesenburg, D.; Sedaghat, Sam; Bürgers, R.; Voit, D.; Proff, P.; Frahm, J.; Krohn, S.; Krohn, Sebastian (Clinical oral investigations, 2025)
Objectives: A novel multi-slice real-time MRI (ms-rtMRI) approach was applied in order to bilaterally investigate temporomandibular joint (TMJ) kinematics during mastication and force-free jaw movements in healthy subjects and individuals with anterior disc displacement (with / without reduction). Materials and methods: Nineteen subjects (mean age 31.2 ± 12.6 years) underwent clinical examination (DC/TMD) and bilateral sagittal-oblique ms-rtMRI on a 3T system with a customized 15-channel mandibular coil, achieving 55.6 ms temporal and 0.5 × 0.5 mm² in-plane resolution. A standardized mastication protocol involving food boluses with increasing elastic modulus (bread, cheese, carrot, caramel) was employed to capture ipsilateral and contralateral joint dynamics. Motion data were analyzed using Generalized Additive Modelling (GAM) after time-normalization in order to identify phase-specific differences in condylar translation and rotation. Results: Force-free mandibular movements demonstrated coupled rotational and translatory excursions averaging 26.3°, 14.3 mm (anteroposterior), and 5.5 mm (craniocaudal). GAM analyses revealed that bolus type generally did not significantly alter TMJ kinematics, except caramel, which transiently affected contralateral rotation. Diagnostic subgroup comparisons showed marked deviations in subjects with anterior disc displacement without reduction (antDDwoR), especially contralaterally, manifesting as temporally extended disturbances in translatory and rotational trajectories. Conclusion: The present approach combined ms-rtMRI with temporally resolved GAM, which effectively revealed diagnosis-specific alterations in TMJ biomechanics during mastication. TMJ kinematics remarkably remained robust even over various food consistencies. However, patients with antDDwoR exhibited temporally and spatially extended deviations in condylar translation and rotation, predominantly during contralateral chewing. Clinical relevance: The present methodology overcomes limitations of established approaches in order to reveal TMJ biomechanics using multidimensional, time-normalized analyses. The results allow for the differentiation between normal and displaced discs during functional loading, which might expand dynamic evaluation of the TMJ in future diagnostic methods.
Online veröffentlicht: 11. Dezember 2025
Gesehen am 09.02.2026